(untitled) (Strathmore Law Journal, 2016)
This paper reviews international standards on political participation by persons with intellectual disabilities and how they are implemented in Kenya. On one hand, Article 25 of the International Covenant on Civil and Political Rights(ICCPR) allows limitation of rights based on ‘reasonable and objective’ criteria. Whereas it is considered unreasonable to restrict participation rights of persons with physical disabilities, General Comment 25 to the ICCPR permits restrictions based on ‘established mental incapacity’. On the other hand, the Convention on the Rights of Persons with Disabilities (CRPD) does not foresee any limitation of participation rights; rather it recognises the freedom of persons with disabilities to be involved in decision-making, including the right to vote and hold public office. Kenya is a party to both instruments, having acceded to the ICCPR in 1972 and ratified the CRPD in 2008. Kenya’s law does not deprive persons with intellectual disabilities of legal capacity. In fact, Article 54(2) of the Constitution of Kenya (2010 Constitution)seeks to increase participation of persons with disabilities in decision making and public life by providing, inter alia, for the progressive inclusion of persons with disabilities in at least five percent of all elective and nominated positions. Whereas Kenya’s law allows for limited guardianship, it is the informal guardianship created by the family, on whom persons with intellectual disabilities are dependent for support, which poses the greatest barrier to the exercise of participation rights. This informal guardianship, combined with negative societal attitudes and ignorance at all levels including the Judiciary, the electoral management body (the Independent Electoral and Boundaries Commission (IEBC)) and even the wider disability movement, makes political participation rights for persons with intellectual disabilities illusory. If the situation of persons with intellectual disabilities is not addressed, only persons with physical and sensory disabilities will be able to take up the affirmative action measure created by Article 54(2) of the 2010 Constitution.